Arquitectura y narrativa : el espacio público como articulador narrativo del lugar (2017)
"This thesis proposes a new way to see Bogota using the narrative as a propositive tool. Understanding from the pedestrian, how the city is a living agent who uses architecture as a stage to materialize everyday life. Under the question of What will be the pedestrian routes with the arrival of the new metro system? The intervention recognizes the dynamics that architecture produces over public space. From a mapping of the different activities (commercial, recreational, domestic and cultural) that occur on the street, it is understood how the uses of the buildings condition the events that occur in the public space, creating typologies in the way in which the pedestrian interacts with this space." -- Tomado del Formato de Documento de Grado.